The Meaning of The Cockfighting Tradition Among the Talang Mamak Tribe in Rantau Langsat Village, Indragiri Hulu - Wulandari, Indah; Kasman, Selvi (Kirana Publisher (KNPub), 2024)
This research examines the tradition of cockfighting among the Talang Mamak tribe in Rantau Langsat Village, Batang Gansal District, Indragiri Hulu Regency, Riau Province. The method used in this research is qualitative method. The data collection techniques obtained from observation, interviews, documentation and literature studies related to the research problem. Data analysis was carried out using symbolic interpretive and functional structural theories. The findings in this study are that there is a meaning given by the Talang Mamak community to the tradition of cockfighting as a religious rite and identity that is contained in its implementation. From this meaning, social, political and economic stratification emerges as well as functional and dysfunctional in the tradition of cockfighting.